2020
DOI: 10.1186/s13071-020-04365-y
|View full text |Cite
|
Sign up to set email alerts
|

Importation of cats and risk of parasite spread: a Caribbean perspective and case study from St Kitts

Abstract: Background In more recent years, international travel with cats has increased. The distribution of cat parasites can change with this movement. Already, subtropical and tropical parasites have been reported by veterinarians in areas where they are not naturally present. Understanding the prevalence of tropical and subtropical parasites in Caribbean islands and the risk of importation to temperate areas could enable improved prevention recommendations and border control import requirements. Methods We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…There is a precipitous decline in occurrence in regions with owned cats that are confined predominately indoors. For example, prevalence in free roaming cats and owned-cats in St. Kitts was reported to be 81 and 6.8%, respectively (Krecek et al 2010, Ketzis et al 2020. This pattern was also reported in a study from Brazil that found free roaming cats (42%) had significantly greater occurrence of infection than confined cats (7.1%) (Salomão et al 2005).…”
Section: Chronic Cholangitis/cholangiohepatitis Associated With Liver...mentioning
confidence: 64%
See 1 more Smart Citation
“…There is a precipitous decline in occurrence in regions with owned cats that are confined predominately indoors. For example, prevalence in free roaming cats and owned-cats in St. Kitts was reported to be 81 and 6.8%, respectively (Krecek et al 2010, Ketzis et al 2020. This pattern was also reported in a study from Brazil that found free roaming cats (42%) had significantly greater occurrence of infection than confined cats (7.1%) (Salomão et al 2005).…”
Section: Chronic Cholangitis/cholangiohepatitis Associated With Liver...mentioning
confidence: 64%
“…2010, Ketzis et al . 2020). This pattern was also reported in a study from Brazil that found free roaming cats (42%) had significantly greater occurrence of infection than confined cats (7.1%) (Salomão et al .…”
Section: Anatomy and Physiology Of The Biliary Systemmentioning
confidence: 99%
“…Los parásitos ciclozoonóticos asociados a perros y gatos ocasionan múltiples enfermedades al hombre (Vilca de Díaz & Melo-Anccasi, 2013;Nunes et al, 2018;Ferraz et al, 2020;Jenkins, 2020;Ketzis et al, 2020), representando un riesgo potencial para la salud humana (Ruiz et al, 2015;Peterson & Barnes, 2020). La alta frecuencia de parásitos intestinales zoonóticos en perros y gatos hace necesarias medidas correctivas y preventivas desde la salud pública para su control (Ortiz-Álvarez, 2015;Sarmiento-Rubiano et al, 2018;Rivero et al, 2020) & Melo-Anccasi, 2013;Ruiz et al, 2015;Rosado-Aguilar et al, 2016;García-Galán et al, 2017;Geng et al, 2018;Sarmiento-Rubiano et al, 2018;López-Osorio et al, 2020;Rostami et al, 2020), lo que evidencia una parasitofauna común.…”
Section: Introductionunclassified